Estimates of growth and productivity of bean by using a mathematical-physiological model - Plá, Gilmar Pezzopane; Lopes, Nei Fernandes (Pesquisa Agropecuaria Brasileira, 1998)
The mathematical-physiological model developed by Miglioranza (1992) was employed to simulate growth and productivity of bean (Phaseolus vulgaris L. cv. Negrito 897) crop for several regions of Minas Gerais State. An estimate of net production of dry matter was made on daily basis, i.e., balance betwen gain (photossynthesis) and loss (respiration). Photosynthesis and respiration rates were estimate using daily global radiation and maximum, minimum, and mean temperatures. The model was shown to be adequate to simulate growth and productivity. For all regions, the intermediate periode between "rainy" and "dry" seasons was suggested as the most indicate for cultivation, since the model estimates good and high productivity of beans. Great productions of biomass and seeds were obtained by simulation of Sete Lagoas and Araxá conditions. Relationship between maximum and potential dry matter production rates varied from 18 to 22%, for all seasons.
Keywords: Phaseolus vulgaris; common bean; photossynthesis